2010
DOI: 10.1517/14728222.2010.487065
|View full text |Cite
|
Sign up to set email alerts
|

The role of endothelin in the pathophysiology of glaucoma

Abstract: Overall, we believe that the body of evidence supports the following conclusions; i) endothelin is a potent vasoconstrictor that plays a role in ocular physiology, ii) endothelin may play a role in the pathophysiology of glaucoma and iii) modulation of the endothelin system with newly discovered potent antagonists holds promise in treating glaucoma through both pressure-dependent and pressure-independent pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…13 Increased IOP is the most important risk factor for glaucoma, but the pathogenesis of glaucoma is multifactorial and unclear. 2,13 The role increased IOP plays in glaucomatous change remains to be elucidated. 2 Studies have shown that some patients might not develop glaucomatous changes despite increased IOP, whereas other patients show evidence of glaucomatous changes in the absence of increased IOP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Increased IOP is the most important risk factor for glaucoma, but the pathogenesis of glaucoma is multifactorial and unclear. 2,13 The role increased IOP plays in glaucomatous change remains to be elucidated. 2 Studies have shown that some patients might not develop glaucomatous changes despite increased IOP, whereas other patients show evidence of glaucomatous changes in the absence of increased IOP.…”
Section: Discussionmentioning
confidence: 99%
“…2,13 The role increased IOP plays in glaucomatous change remains to be elucidated. 2 Studies have shown that some patients might not develop glaucomatous changes despite increased IOP, whereas other patients show evidence of glaucomatous changes in the absence of increased IOP. 2,20,21 Ischemia and vascular dysregulation have been implicated in the pathogenesis of GON, and ET-1 has been demonstrated to be a key player in regulation of ocular perfusion and perhaps in the overall pathogenesis of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, previous studies demonstrated that patients with glaucoma, in contrast to the control subjects, have an abnormal hyperactivity of ET-1 in response to vasospastic stimuli such as cold. 58 It has been postulated that an imbalance between vasoconstrictor substances such as 59,60 It was reported that patients with glaucoma who have vasospasm have a higher susceptibility to glaucomatous damage, which could be a consequence of a decreased dilation of blood vessels that properly autoregulate blood flow. 55 If our speculation is correct, BCACs induce normalization of ET-1, and its receptor balance may be beneficial for ocular blood circulation, since an increased ET-1 reactivity could lead to decreased ocular blood flow as indicated above.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments demonstrated that oral administration of the BCACs significantly improved dark adaptation and video display terminal work-induced transient refractive alteration in healthy human volunteers [15]. In terms of the relationship between ET-1 and the eye, some investigations have shown that ET-1 receptors are present in human uveal tissues [38], retina and ONH [39], suggesting that ET-1 may be implicated in ischemic vascular diseases such as diabetic retinopathy [40], retinal vein occlusion and retinal artery occlusion [41] and glaucoma [42,43,44,45]. Previous studies have shown that statistically significant differences of plasma ET-1 levels exist in glaucoma patients as compared to those in control subjects [12,43,46,47].…”
Section: Discussionmentioning
confidence: 99%